The Marquess next door - Heath, Virginia, 1968- (Heath, Virginia, 1968- Talk of the Beau Monde., 2021)
When Lucius, Marquess of Thundersley, comes to Miss Hope Brookes' rescue at a ball, Hope finds it harder and harder to ignore her handsome new neighbor.